BUDGETING ORGANIZATION IN MANAGEMENT ACCOUNTING MODULE - Elena A. Sharovatova (Advanced Engineering Research, 2011)
The algorithm for the interconnection of the economic activity effective indicators at the level of the management accounting and budgeting is offered. The budgeting technique based on the single structure of the budget-accountable control objects is considered. The transfer pricing mechanism for cost centres and responsibility centres which permits to plan inside prices for such control objects is developed.